A randomized controlled trial to assess the efficacy of an interactive mobile messaging intervention for underserved smokers: Project ACTION - Vidrine, Damon J; Fletcher, Faith E; Danysh, Heather E; Marani, Salma; Vidrine, Jennifer Irvin; Cantor, Scott B; Prokhorov, Alexander V (BMC public health, 2012)
Background Despite a significant decrease in smoking prevalence over the past ten years, cigarette smoking still represents the leading cause of preventable morbidity and mortality in the United States. Moreover, smoking prevalence is significantly higher among those with low levels of education and those living at, or below, the poverty level. These groups tend to be confronted with significant barriers to utilizing more traditional smoking cessation intervention approaches. The purpose of the study, Project ACTION (Adult smoking Cessation Treatment through Innovative Outreach to Neighborhoods), is to utilize a mobile clinic model, a network of community sites (i.e., community centers and churches) and an interactive mobile messaging system to reach and deliver smoking cessation treatment to underserved, low-income communities. Methods/Design We are using a group-randomized design, with the community site as the sampling unit, to compare the efficacy of three smoking cessation interventions: 1) Standard Care - brief advice to quit smoking, nicotine replacement therapy (NRT), and self-help materials; 2) Enhanced Care - standard care components plus a cell phone-delivered text/graphical messaging component; and 3) Intensive Care - enhanced care components plus a series of 11 cell phone-delivered proactive counseling sessions. An economic evaluation will also be performed to evaluate the relative cost effectiveness of the three treatment approaches. We will recruit 756 participants (252 participants in each of the 3 intervention groups). At the time of randomization, participants complete a baseline assessment, consisting of smoking history, socio-demographic, and psychosocial variables. Monthly cell phone assessments are conducted for 6 months-post enrollment, and a final 12-month follow-up is conducted at the original neighborhood site of enrollment. We will perform mixed-model logistic regression to compare the efficacy of the three smoking cessation intervention treatment groups. Discussion It is hypothesized that the intensive care approach will most successfully address the needs of the target population and result in the highest smoking cessation rates. In addition to increasing cessation rates, the intervention offers several features (including neighborhood outreach and use of mHealth technology) that are likely to reduce treatment barriers while enhancing participant engagement and retention to treatment. Trial registration This randomized controlled trial is registered with clinicaltrials.gov registration number NCT00948129.